(untitled) (Philological Studies, 2023)
The Coronavirus/COVID-19 pandemic has presented new ways of perceiving reality which automatically reflected on how we understand, read and think about certain works of art and works of fiction. Such an example is the novel Rabies (1985) by Borislav Pekić which, in this paper, is interpreted through Bauman’s concept of “liquid fear” (2018). In this way, we are trying to show that fiction has somewhat involuntarily “predicted” the COVID-19 world pandemic. This does not mean that Rabies should be read as a prophecy of what started in 2019 but rather as a proof that fiction sometimes has its roots in reality (it is inspired by true events). Fiction, more often than not, presents a reflection of past experiences that can be recognized even in today’s contemporary world. Thus, the paper examines the main hypothesis that the “liquid fear” present in the novel “Rabies” can be seen as equivalent of the “liquid fear” with which we deal on a daily basis ever since the beginning of the COVID-19 world pandemic. We used the general methods of analysis and synthesis, in order to present those aspects of the novel that are important for the understanding of the fictitious epidemic in the novel, and the comparative method, which juxtaposes fiction and reality. Through the conclusion of the paper, we should understand how the descriptions of the epidemic in the novel affect our perception and understanding of the current world pandemic and how the described events in the novel serve as a valid reflection of certain aspects of our approach towards the COVID-19 pandemic.